Exploring the Influence of Smart Tourism Technology and e-WOM on Tourist Citizenship Behavior in Urban Ecotourism - Galuh Ajeng Ayuningtiyas; Fedianty Augustinah; dian ferriswara; Priyanto; Amirul Mustofa (Akademi Komunitas Negeri Putra Sang Fajar Blitar, 2026)
Introduction: The rapid development of digital technology has significantly transformed the tourism industry, particularly through the implementation of smart tourism technology and the increasing influence of electronic word-of-mouth (e-WOM). These digital factors are considered important in shaping tourist behavior, including Tourist Citizenship Behavior (TCB), which reflects voluntary actions such as recommending destinations, helping other tourists, and providing feedback. This study aims to examine the influence of smart tourism technology and e-WOM on TCB in the context of the Mangrove Botanical Garden Surabaya. Methods: This study employs a quantitative approach using a cross-sectional survey design. Data were collected through an online questionnaire from 382 respondents, determined using the Krejcie and Morgan sampling table. The sampling technique used was purposive sampling, targeting tourists who had visited the destination and were exposed to digital tourism platforms. Data were analyzed using multiple linear regression with SPSS, including validity, reliability, classical assumption, and hypothesis testing. Results: The results show that smart tourism technology and e-WOM simultaneously have a positive and significant effect on Tourist Citizenship Behavior (F = 77.156; p < 0.05). Partially, smart tourism technology has a positive and significant effect on TCB (β = 0.607; p < 0.05), while e-WOM has a positive but not significant effect (β = 0.228; p > 0.05). The coefficient of determination (R²) indicates that 61.6% of TCB is explained by the independent variables. Smart tourism technology is identified as the most dominant factor influencing TCB. Discussion: These findings highlight the critical role of smart tourism technology in enhancing tourist engagement and encouraging voluntary behaviors that support destination sustainability. While e-WOM contributes to shaping perceptions, its direct influence on behavioral outcomes is limited. The study emphasizes the importance of digital experience in fostering active tourist participation and provides insights for improving tourism management strategies in ecotourism destinations.